Zur Berechnung des "maßgeblichen Außenlärmpegels" und des "maßgeblichen Innenlärmpegels" sowie der Schallpegeldifferenz "außen/innen" bei Fluglärm in Anlehnung an DIN 4109, VDI 2719, DIN EN ISO 140-5 und DIN EN ISO 717-1. Teil 1. - Augustin, Erhard; Feldmann, Joachim; Maschke, Christian (Springer-VDI-Verl., 2006)
In Analogie zu Betrachtungen bezüglich der Schalldämmung von Gebäude-Außenbauelementen gegenüber einer Schalleinwirkung durch Straßenverkehr werden im ersten Teil methodisch vergleichbare Berechnungen vorgenommen, um die Schalldämmung von Gebäude-Außenbauelementen bei Flugverkehr zu beschreiben. Hier ergeben sich in Abhängigkeit von der Lage des Immissionsortes zur Flugbahn unterschiedliche wirksame Bauschalldämmmaße, die durch den jeweiligen Schall-Einfallswinkel bedingt sind, d.h. von der Sichtentfernung des Immissionsortes zur Flugbahn abhängen. Da diese stark variieren, lässt sich die Schalldämmung der jeweiligen Gebäudefassade nicht mehr befriedigend durch einen für alle Immissionsorte gleichen Zuschlag zum berechneten bzw. gemessenen Labor-Schalldämmmaß bestimmen, mit der Folge, dass auch die Schallpegeldifferenz "außen/innen" keinen konstanten Wert aufweisen kann. Zur Ermittlung der wirksamen Schallpegeldifferenz muss in Abhängigkeit von der momentanen Position eines vorbei fliegenden Flugzeugs der Innenraumpegel kontinuierlich bestimmt werden. Die für einen Immissionsort "maßgebliche" Schallpegeldifferenz "außen/innen" ergibt sich dann als die geringste Differenz zwischen dem momentanen Innenraumpegel und dem zum gleichen Zeitpunkt wirksamen Freifeld-Außenschallpegel, im Laufe eines Überflugs. Aufgrund der Besonderheiten des Flugverkehrs ist es unzulässig, die für Straßenverkehr gültigen Gleichungen zur Berechnung der "maßgeblichen" Schallpegeldifferenz unverändert zu übertragen. difu

In analogy to calculations of Kötz regarding external building elements sound insulation against road traffic noise, methodically comparably investigations were carried out to describe the sound insulation of external building elements against air traffic noise. While for road traffic the effective sound insulation can be adequately assessed by a constant surcharge of 3 dB to the calculated or measured laboratory-sound insulation, in the case of the air traffic a constant surcharge is problematic. Depending on the viewing distance between the immission place and the flight path, different sound insulations are effective, according to the different angles of the flight noise radiation. Since the viewing distance varied with air traffic very strongly, and the real sound absorption of the building façades can no longer be satisfactorily determine by a constant surcharge of the calculated or measured laboratory-sound insulation for all immission places. This has the consequence that the sound pressure level difference outside/inside also cannot show a constant value for all immission places. For the determination of a valid sound pressure level difference the effective interior level must be calculated continuously dependently of the short-term position of the flying airplane. The authoritative sound pressure level difference for an immission place is then given by the lowest difference between the short-term interior level and the corresponding effective free field noise level outside, during the course of an over-flight. At this point an unusual feature was discovered, that for immission places near by the flight path the highest interior levels, and with that the lowest effective sound pressure level difference, do not appear at the time of the shortest viewing distance, but rather before and/or after this time. During the time of the shortest viewing distance the noise level difference can be considerably higher than the authoritative noise level difference for the immission place. Due to the before mentioned particular features of the air traffic it is unacceptable to use the valid equations for the calculation of the authoritative sound pressure level difference for road traffic, unchanged for air traffic. If the described knowledge is used to calculate the interior noise level for a window opened to tilt in the most exposed façade, at given free field noise level outside, it can be shown statistically which typical sound pressure level differences are effective for immission places with longer flight path distances and shorter flight path distances. As a result, for long flight path distances with elevation angles of the flight noise radiation below approx. 60°, the effective sound pressure level differences is about 2 dB lower than for road traffic with windows open to tilt, as well as for closed windows. If interior maximum levels for aircraft noise are to be calculated from free field maximum level outside without consideration of the flight noise radiation, a sound pressure level difference of 13 dB is used for a window opened to tilt to protect immission places with longer flight path distances adequate.
To the calculation of the "authoritative outside noise level" and the "authoritative interior noise level" as well as the sound pressure level difference outside/inside with aircraft noise according to DIN 4109, VDI 2719, DIN EN ISO 140-5 and DIN EN ISO 7.
Keywords: Umweltschutz; Lärmbelastung; Lärm; Fluglärm; Innenraum; Außenraum; Schall; Schallschutz; Immissionsschutz; Prognose; Akustik; Berechnungsverfahren; DIN; Schalldämmung